PROFIL GAYA KEPEMIMPINAN PELATIH SEPAKBOLA BERLISENSI C AFC PADA AKADEMI AREMA FC DAN AKADEMI ASIFA KOTA MALANG - Wildan Yahya Suryaditya; Supriatna; Yulingga Nanda Hanief; Imam Hariadi (Cahaya Ilmu Bangsa Institute, 2024)
The purpose of this research is to identify the dominant leadership styles applied by licensed C AFC coaches at AREMA FC Academy and ASIFA Academy in Malang City. This study is descriptive research with a quantitative approach, employing a survey method. The sample consists of coaches who are eligible for C AFC licensure, totaling 6 from AREMA FC Academy and 4 from ASIFA Academy. Data analysis in this research utilizes categorization and percentage analysis. The results indicate that the dominant leadership style among C AFC licensed coaches at ASIFA Academy in Malang City is democratic leadership with a percentage of 50%. However, the significant proportions of authoritarian, people-centered, and task-oriented styles suggest that coaches need to possess high adaptation skills. On the other hand, coaches at AREMA FC Academy exhibit a balanced adoption of all four leadership styles (authoritarian, democratic, people-centered, and task-oriented) with a percentage of 50%. This conclusion confirms that coaches at both academies need to integrate various leadership styles to meet the needs and dynamics of athlete training.